PENGARUH RETURN ON ASSET (ROA), EARNING PER SHARE (EPS), NET PROFIT MARGIN (NPM), DAN PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2021 - Simanjuntak, Adi; Silalahi , Esli; Silalahi, Donalson (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2023)
The purpose of this research is to know and explain the effect Return On Assets (ROA), Earning Per Share (EPS), Net Profit Margin (NPM), and Price Earning Ratio (PER) on stock prices in LQ-45 companies listed on the Indonesia Stock Exchange in 2018-2021 both simultaneously and partially.The population in this study were 45 companies. The sampling technique used was a purposive sampling technique so that a sample of 18 companies was obtained with a 4-year research period. The analysis technique used is a multiple linear regression model by conducting the t test and F test. The results of the t test show that the variable Return On Assets (ROA) has a positive and significant effect on stock prices, Earning Per Share (EPS) has a positive and significant effect on stock prices, Net Profit Margin (NPM) has a positive and significant effect on stock prices, and Price Earning Ratio (PER) has a positive and significant effect on stock prices in LQ-45 companies listed on the Indonesia Stock Exchange in 2018-2021 The results of the F test indicate that Return On Assets (ROA), Earning Per Share (EPS), Net Profit Margin (NPM) and Price Earning Ratio (PER) have a significant effect on stock price of listed LQ-45 companies on the Indonesia Stock Exchange in 2018-2021. The coefficient of determination of 88.8% means that variations Return On Assets (ROA), Earning Per Share (EPS), Net Profit Margin (NPM), and Price Earning Ratio (PER) are able to explain variations in stock prices of 8.8%. the remaining 11.2% is influenced by other variables